2021
DOI: 10.3390/jcm10163493
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Rapid Antigen Test Kits for Detecting SARS-CoV-2: A Systematic Review and Meta-Analysis of 17,171 Suspected COVID-19 Patients

Abstract: Early diagnosis is still as crucial as the initial stage of the COVID-19 pandemic. As RT-PCR sometimes is not feasible in developing nations or rural areas, health professionals may use a rapid antigen test (RAT) to lessen the load of diagnosis. However, the efficacy of RAT is yet to be investigated thoroughly. Hence, we tried to evaluate the overall performance of RAT in SARS-CoV-2 diagnosis. Based on our PROSPERO registered protocol (CRD42021231432), we searched online databases (i.e., PubMed, Google Scholar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 58 publications
8
70
3
2
Order By: Relevance
“…RT-PCR is used to detect reinfection cases after vaccination. Mass testing with highly sensitive rapid antigen testing (RAT), capable of detecting COVID-19 infection in the acute phase, is crucial in monitoring reinfection cases post-vaccination [240][241][242]. Vaccine antigen-specific sero-monitoring and memory T/B-cell persistence are also essential determinants for the requirement of booster doses and epitope modification in vaccine designing.…”
Section: Importance Of the Integration Of Diagnostic Assays Pre-and Post-vaccinationmentioning
confidence: 99%
“…RT-PCR is used to detect reinfection cases after vaccination. Mass testing with highly sensitive rapid antigen testing (RAT), capable of detecting COVID-19 infection in the acute phase, is crucial in monitoring reinfection cases post-vaccination [240][241][242]. Vaccine antigen-specific sero-monitoring and memory T/B-cell persistence are also essential determinants for the requirement of booster doses and epitope modification in vaccine designing.…”
Section: Importance Of the Integration Of Diagnostic Assays Pre-and Post-vaccinationmentioning
confidence: 99%
“…Before this study, we previously assumed that COVID-19 and dengue diagnoses could be affected by a misclassification bias which could stem from the poor sensitivity of both SARS-CoV-2 molecular and DENV NS1 antigen tests rather than from their false positives [ 9 ]. This putative bias was believed to be minimal given that, firstly, on Reunion Island, like anywhere else during the rise of the COVID-19 pandemic [ 21 ], there was little cocirculation of other respiratory viruses that could have competed with SARS-CoV-2 and caused false negatives, [ 22 ], and secondly, for COVID-19, negative samples were retested by RT-PCR upon onset of new symptoms, meaning that rapid antibody or antigenic tests were ruled out, while for dengue, the workup was completed by a RT-PCR or a serology test to downsize false negative and false positive proportions [ [23] , [24] , [25] ]. This caution decision rule likely pledges the diagnostic accuracy of our gold standards.…”
Section: Discussionmentioning
confidence: 99%
“…At an individual risk level, predictions should be guided using first of all calibration performances (calibration plots and goodness-of-fit metrics) [ 25 ]. Our findings showed that the calibration of the models ( Tables S6–S8 ) and their derived scores ( Table S9 ) were excellent and consensual for dengue which enables individual risk prediction and satisfactory for COVID-19 which suggests caution for individual risk prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications have identified the sensitivity and specificity of other antigen-detection methods, including a meta-analysis of 29 studies on rapid antigen tests that indicate overall pooled sensitivity and specificity as 68% and 99% [ 38 ], and a recent large-scale study on a rapid antigen test (Roche/SD Biosensor) has shown similar diagnostic accuracy with 65% sensitivity and 100% specificity [ 39 ]. The immunofluorescence assay yields comparable sensitivity of 59% and specificity of 98%, owing to cross-reactivity with SARS-CoV.…”
Section: Discussionmentioning
confidence: 99%